2013
DOI: 10.5897/ajmr12.1586
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of culturable aerobic bacteria colonizing four petroleum by-products storage reservoirs

Abstract: The petroleum reservoirs are commonly exposed to bacterial contamination. The proliferation of several bacterial species, could modify the product quality, change viscosity, help other sulfatereducing, iron reducing bacteria to grow, and accelerate reservoir biocorrosion. Thus, companies of storage and transport of petroleum frequently use biocides to prohibit bacterial proliferation. However, the use of the appropriate biocide, need an obvious knowledge of bacterial population harbouring the reservoir. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The transitions are accompanied with reaction changes both in the contaminated soil without any preparation as well as after adding it, what may be caused by the metabolic microorganisms activity (Krzyśko-Łupicka et al 2013, Rosik-Dulewska et al 2015 The vulnerability of n-alkanes on biodegradation depends on the chemical structure of hydrocarbons and their molecular mass; hydrocarbons degradation of the chains length C10-C22 takes place in the fastest way and the other groups characterized by high hydrophobicity are disintegrated in a much more difficult way (Dindar et al 2013;Hamed et al 2013). In our research, we have shown that the bioremediation stimulation with Fyre-Zyme preparation and with calcium carbonate was 084 p = ---p = 0.623 p = 0.991 p = 0.276 p = 0.916 Content of n-alkanes C 0.377 1.000 0.556 0.855 0.562 p = 0.623 p = ---p = 0.444 p = 0.145 p = 0.438 Content of n-alkanes FZ 0.009 0.556 1.000 0.609 0.997* p = 0.991 p = 0.444 p = ---p = 0.391 p = 0.003 Content of n-alkanes Ca 0.724 0.856 0.609 1.000 0.652 p = 0.276 p = 0.145 p = 0.391 p = ---p = 0.348 Content of n-alkanes FZ+Ca 0.084 0.562 0.997* 0.652 1.000 p = 0.916 p = 0.438 p = 0.003 p = 0.348 p = ---*Shown correlation significant at the level p < 0.05 leading to a decrease of long-chain hydrocarbons content (C28, C36, and C38).…”
Section: Resultsmentioning
confidence: 99%
“…The transitions are accompanied with reaction changes both in the contaminated soil without any preparation as well as after adding it, what may be caused by the metabolic microorganisms activity (Krzyśko-Łupicka et al 2013, Rosik-Dulewska et al 2015 The vulnerability of n-alkanes on biodegradation depends on the chemical structure of hydrocarbons and their molecular mass; hydrocarbons degradation of the chains length C10-C22 takes place in the fastest way and the other groups characterized by high hydrophobicity are disintegrated in a much more difficult way (Dindar et al 2013;Hamed et al 2013). In our research, we have shown that the bioremediation stimulation with Fyre-Zyme preparation and with calcium carbonate was 084 p = ---p = 0.623 p = 0.991 p = 0.276 p = 0.916 Content of n-alkanes C 0.377 1.000 0.556 0.855 0.562 p = 0.623 p = ---p = 0.444 p = 0.145 p = 0.438 Content of n-alkanes FZ 0.009 0.556 1.000 0.609 0.997* p = 0.991 p = 0.444 p = ---p = 0.391 p = 0.003 Content of n-alkanes Ca 0.724 0.856 0.609 1.000 0.652 p = 0.276 p = 0.145 p = 0.391 p = ---p = 0.348 Content of n-alkanes FZ+Ca 0.084 0.562 0.997* 0.652 1.000 p = 0.916 p = 0.438 p = 0.003 p = 0.348 p = ---*Shown correlation significant at the level p < 0.05 leading to a decrease of long-chain hydrocarbons content (C28, C36, and C38).…”
Section: Resultsmentioning
confidence: 99%